Person-Organization Fit and Employee Performance: Mediation Role Job Satisfaction and Organizational Commitment - Jufrizen Jufrizen; Hazmanan Khair; Ade Putra Wijaya Siregar; Weni Hawariyuni (LPPM Universitas Terbuka, 2023)
Purpose – This study aimed to investigate and assess the effect of person-organization fit (POF) on employee performance (EP), with job satisfaction (JS) and organizational commitment (OC) acting as mediators. Methodology – Questionnaires were used in this quantitative study, to obtain information from 61 employees, with subsequent analysis implementing the Structural Equation Model SmartPLS 4.0. Results – The results showed that EP was significantly influenced by POF, JS, and OC. This indicated that POF relevantly influenced employee JS. POF and JS also significantly influenced OC. Moreover, the compatibility between employees and organization significantly influenced EP through JS and OC. POF also substantially influenced OC, mediated by JS. Based on the mediation by OC, JS then significantly influenced EP. Originality – This study investigated the employee issues that significantly and widely impacted organizational performance. It also provided a deeper comprehension of the personal relationships between organization fit, employee engagement, and JS.